The Influence of Learning Environment, Lecturer Knowledge, and Personal Initiative on Learning Process and Graduate Quality: a Structural Equation Modeling Approach - Irfansyah, Ade; Suparji Suparji; Bambang Suprianto (East Asian Journal of Multidisciplinary Research, 2024)
This study aims to analyze the influence of the learning environment, lecturer knowledge, and personal initiative on the learning process and graduate quality in higher education institutions. The methodology employed is Structural Equation Modeling (SEM) to test the relationships among these variables. The results indicate that a conducive learning environment and adequate lecturer knowledge significantly contribute to the learning process. Additionally, students’ personal initiative also positively impacts graduate quality. These findings provide essential insights for educational managers to create a better learning environment and enhance teaching quality in efforts to improve graduate outcomes.